Investment Decisions as a Moderator in Capital Structure, Firm Size, Profitability, and Firm Value - Erni Ghuri; Zulfikar Zulfikar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research investigates how financial leverage, firm size, and profitability influence firm valuation, with capital allocation choices examined as a moderating variable. Specifically, it seeks to answer whether these financial factors significantly affect firm value and whether investment decision proxies strengthen these relationships. Utilizing a quantitative approach, the study analyzes secondary data from the financial statements of conventional banks listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022. Multiple linear regression assesses direct effects, while moderated regression analysis tests the interaction effects using SPSS software. Financial leverage is measured through the debt-to-equity ratio (DER), firm size by the natural logarithm of total assets (Ln), profitability by return on equity (ROE), capital allocation choices by the price-earnings ratio (PER), and firm valuation by price-to-book value (PBV). Findings reveal that financial leverage and profitability significantly influence firm valuation, while firm size does not. The lack of significance for firm size may reflect that larger banks in Indonesia are not inherently more efficient or value-generating due to structural or operational inefficiencies. Capital allocation choices have a direct, positive effect on firm valuation, but moderate the impact of profitability, rather than leverage or size. This suggests that investors prioritize profitability when making valuation-based investment decisions. These results are consistent with prior studies that highlight the dominant role of profitability in driving firm value, particularly in emerging markets, where size alone does not guarantee performance or market perception.